Інформаційна система геометричного моделювання функціональних поверхонь каналів турбокомпресорів дизельних двигунів - Щербина, Віктор Михайлович; Щербина, Виктор Михайлович; Shcherbyna, Viktor; Мацулевич, Олександр Євгенович; Мацулевич, Александр Евгеньевич; Matsulevych, Oleksandr (My University, 2015)
UK: Проектування конструкцій складних функціональних поверхонь, що графічно відображають зміни перебігу процесу та задовольняють технічним і ергономічним вимогам, є одним з важливих напрямків наукових досліджень у техніці, а саме в розрахунках каналів та проточних частин турбокомпресорів, каналів двигунів внутрішнього згоряння, аеро- і гідродинамічних поверхонь. EN: In work information system of discrete interpolation of dot lines for designing a skeleton of the channel of a snail turbocompressor the diesel engine with application of a method of discrete geometrical modelling on the basis of median perpendiculars. Program realization of an offered method provides an opportunity of the task the user of parameters of sections of a skeleton of a channel urface as coordinates of points of discretely submitted curve (DSC), preservation of coordinates DSC, export of the data from preliminary created file, interpolation initial DSC, automatic construction of a surface of the channel turbocompressor on the basis of designed coordinates DSC in system of automated designing SolіdWorks, automatic carrying out of the analysis of the simulated surface on conformity air-and to hydrodynamical requirements with the help of software product FlowSіmulatіon, a correcting of an arrangement of points directly in Solіd Works and record of the received coordinates of points ДПК in a corresponding file. The architecture of information system submitted in figure 1.
Information system of geometrical modelling of functional surfaces of channels turbocompressors diesel engines
Keywords: дизельні двигуни; моделювання; конструкції; проектування; техніка; технічні вимоги; турбокомпресор; точковий ряд; координати